2006
DOI: 10.1002/ejoc.200600612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Amphiphilic Glycoconjugates and Glycoclusters

Abstract: Glycolipids are involved in many cellular recognition processes, so there is a need for their synthesis as well as for the design and preparation of glycolipid mimetics. In addition to the application of glycolipid mimetics in a glycobiological context, they are also of interest in many other fields of research, due to their amphiphilic characters. Our goal was to elaborate a series of known orthogonally functionalized glycomimetics and cluster glycosides into glycomimetics of a glycolipid type, so monosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The cores of glycodendrimers are mostly based on classic ones (most frequently PAMAM, ,,,, but also PPI, ,,,– polypropylamine, ,, carbosilane, silsesquioxane, polyphenylene, etc ,– cyclodextrins, cycloveratrylene, calixarene, ,– calix(4)resorcarene (Figure ), carbopeptides ,, ), porphyrin, fullerene, transition metal (Cu 2+ ) bipyridyl, and cyclic decapeptide template. …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The cores of glycodendrimers are mostly based on classic ones (most frequently PAMAM, ,,,, but also PPI, ,,,– polypropylamine, ,, carbosilane, silsesquioxane, polyphenylene, etc ,– cyclodextrins, cycloveratrylene, calixarene, ,– calix(4)resorcarene (Figure ), carbopeptides ,, ), porphyrin, fullerene, transition metal (Cu 2+ ) bipyridyl, and cyclic decapeptide template. …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Using carbohydrates as core molecules for creating clusters as probes for many purposes in the life sciences, also as chiral scaffolds, 15 is quite common 1632 but to our knowledge making carbohydrate clusters by attaching fragments of O-SPs to cores by click chemistry and attaching the resulting cluster of antigens to carrier proteins by squaric acid chemistry to make neoglycoconjugate vaccines for bacterial diseases has not been explored. Here, we propose carbohydrates as convenient starting materials to form tailor-made core subcarriers for making clustered immunogens/vaccines.…”
Section: Resultsmentioning
confidence: 99%
“…The carbohydrate moiety selected for the functionalization of the lipid-dendron hybrids was α-galactose (α-Gal). 30 There are currently very few examples of multivalent assemblies presenting α-galactose. 23,38 Although terminal α-galactose moieties are found in other mammals, they are not normally found in humans.…”
Section: Design Of Carbohydrate-dendron-lipid Hybridsmentioning
confidence: 99%
“…[24][25][26][27] In addition, the step-wise synthesis of dendrons affords well-defined products, allowing the number of peripheral groups to be carefully controlled. Carbohydratefunctionalized dendrons have been conjugated to the hydrophilic blocks of polymer vesicles, 28,29 and have also served as the hydrophilic blocks of amphiphiles where linear or dendritic hydrocarbons [30][31][32][33][34][35][36][37] or polypeptides 38 have served as the hydrophobic blocks. Percec et al reported that amphiphilic Janus glycodendrimers could self-assemble into a wide range of hard and soft assemblies including spherical and tubular vesicles, rod-like micelles, cubosomes, and solid lamellae depending on the chemical structures of their hydrophobic and carbohydratefunctionalized hydrophilic dendrons.…”
Section: Introductionmentioning
confidence: 99%